The effect of transformational leadership on innovative work behavior with moderating role of internal locus of control and psychological empowerment - Qing, Zhang; Abdullah, Abdul Rashid; Hossana, Dalowar; Zongxiang, Hou (Growing Science, 2020)
The current study examined the effect of the style of transformational leadership on innovative work behavior as well as the internal locus of control’s moderating role and psychological empowerment between the relationships of them. We collected data from 422 respondents who are related to family business in Malaysia. Path coefficient analysis was employed to test the hypotheses and SPSS software was used for analyzing descriptive data. The results showed that transformational leadership style, psychological empowerment and internal locus of control have affirmative relationship and significant impact on innovative work behavior. Finally, psychological empowerment and internal locus of control were not found to have moderating effect between innovative work behavior and the style of transformational leadership.